2022
DOI: 10.3390/ijms23105745
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of an Immortalized Human Microglial Cell Line as a Tool for the Study of Diabetic Retinopathy

Abstract: The complexity of the retinal structure reflects on the difficulty to describe its composite cell interactions. Microglia is responsible for the immune reaction to inflammatory stimuli during diabetic retinopathy (DR), but most studies still use rodent cells. We characterized a commercially available immortalized human microglial line and tested its susceptibility to inflammation, to study the interactions between the neuro-vascular retinal portions in species-specific models. After checking the expression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 56 publications
2
9
0
Order By: Relevance
“…We generated mammalian expression plasmids encoding human TREM2 fused to a C-terminal V5 tag and TurboID (TREM2-V5-TurboID) (Figure 1A). TREM2-V5-TurboID was transfected into the human microglial cell line, IM-HM (Mazzeo et al, 2022). Western bloting with antibodies against V5-tag or TREM2 revealed that TREM2-V5-TurboID is expressed with the predicted size (Figure 1B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We generated mammalian expression plasmids encoding human TREM2 fused to a C-terminal V5 tag and TurboID (TREM2-V5-TurboID) (Figure 1A). TREM2-V5-TurboID was transfected into the human microglial cell line, IM-HM (Mazzeo et al, 2022). Western bloting with antibodies against V5-tag or TREM2 revealed that TREM2-V5-TurboID is expressed with the predicted size (Figure 1B).…”
Section: Resultsmentioning
confidence: 99%
“…1A). TREM2-V5-TurboID was transfected into the human microglial cell line, IM-HM (Mazzeo et al, 2022). Western blotting with antibodies against V5-tag or TREM2 revealed that TREM2-V5-TurboID is expressed with the predicted size (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We then studied via RT-PCR the expression of specific mRNAs encoding for pro-inflammatory/pro-angiogenic proteins, whose choice was guided by extensive research in the literature (as detailed in Section 3 ), and our previous research findings [ 23 , 24 ]. We found increased expression of the chemokine (C-C motif) ligand 2 (CCL2), the matrix metalloproteinase-2 (MMP2), and the matrix metalloproteinase-9 (MMP9) in EVs derived from M1-stimulated microglia ( Figure 1 a), and no variations in vascular cell adhesion molecule-1 (VCAM-1).…”
Section: Resultsmentioning
confidence: 99%
“…In all cases, the addition of thiamine to the M1 cocktail resulted in a significant reduction in their expression ( p < 0.05 vs. M1-EVs). In the context of miRNA analysis, we considered our prior results on M1-activated microglia [ 24 ] and circulating extracellular vesicles from diabetic patients with diabetic retinopathy [ 16 ], in order to identify three miRNAs closely associated with inflammation and angiogenesis (mir21, miR146a, and miR155). We evaluated their expression in EVs, finding 10.5-fold increased concentrations of miR21 ( p < 0.001 vs. ctrl) and 2.9-fold augmented miR155 ( p < 0.05) in M1-EVs, and normalization by the addition of thiamine to M1 in microglial cultures ( Figure 1 b).…”
Section: Resultsmentioning
confidence: 99%
“…In our previous study, the CHME3 human microglial cell line was found to be highly permissive to CHIKV infection ( Qadri et al., 2022 ). The recently immortalized C20 human microglial cell line has been used to understand neuropathogenesis of Human Immunodeficiency Virus (HIV), integration of HIV-1 in microglial cells and neuroinflammation ( Mazzeo et al., 2022 ; Rheinberger et al., 2023 ). Hence, we were interested in exploring the potential of CHIKV-infected C20 microglial cells as a model for studying neuropathogenesis of this virus.…”
Section: Discussionmentioning
confidence: 99%